Phase Field Models Versus Parametric Front Tracking Methods: Are They Accurate and Computationally Efficient? (Communications in Computational Physics, 2018)
We critically compare the practicality and accuracy of numerical approximations of phase field models and sharp interface models of solidification. Here we focuson Stefan problems, and their quasi-static variants, with applications to crystal growth.New approaches with a high mesh quality for the parametric approximations of the resulting free boundary problems and new stable discretizations of the anisotropic phasefield system are taken into account in a comparison involving benchmark problemsbased on exact solutions of the free boundary problem.